Efektivitas Metode Penyuluhan Berbasis Multimedia terhadap Peningkatan Pengetahuan tentang Penyakit Jantung Koroner pada Kalangan Pelajar - Irfan Sazali Nasution; Citra Syahrani; Khansa Kanastri Santoso; Lifira Naila Salsabila; Dea Fadilla; Alysa Rahmadani Hasibuan; Novita Rahmayanti Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to evaluate the effectiveness of multimedia-based counseling methods in improving knowledge about Coronary Heart Disease (CHD) among students. Using a pre-experimental one group pre-test and post-test design, 27 students aged 15-17 years participated in the study. The results of the analysis showed a significant increase in participants' knowledge of CHD after the educational intervention, with some statements showing a change from incorrect to correct answers. These findings confirm that multimedia education is effective in delivering health information in an engaging and easy-to-understand manner, and is important for increasing health awareness among adolescents.